2011
DOI: 10.1007/s00430-011-0217-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cord blood myeloid dendritic cells by Trypanosoma cruzi and parasite-specific antibodies, proliferation of CD8+ T cells, and production of IFN-γ

Abstract: We previously reported that Trypanosoma cruzi, the agent of Chagas disease, induces in congenitally infected fetuses a strong, adult-like parasite-specific CD8(+) T cell response producing IFN-γ (Hermann et al. in Blood 100:2153-2158, 2002). This suggests that the parasite is able to overcome the immaturity of neonatal antigen presenting cells, an issue which has not been previously addressed. We therefore investigated in vitro the ability of T. cruzi to activate cord blood DCs and compared its effect to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 78 publications
2
16
0
1
Order By: Relevance
“…The results obtained in the identiWed gated population are presented as percentage of cells expressing the analysed marker, and as MFI of the cell population, after having subtracted the value of the MFI obtained with the isotype-matched control mAb. The expression levels of co-stimulatory molecules on mDCs incubated with unlabelled or CSFE-labelled trypomastigotes were similar and as described previously [34], indicating that CSFE did not interfere with the process of activation or with analyses performed by Xow cytometry (data not shown).…”
Section: Flow Cytometry Analysis Of Leucocytesmentioning
confidence: 59%
See 3 more Smart Citations
“…The results obtained in the identiWed gated population are presented as percentage of cells expressing the analysed marker, and as MFI of the cell population, after having subtracted the value of the MFI obtained with the isotype-matched control mAb. The expression levels of co-stimulatory molecules on mDCs incubated with unlabelled or CSFE-labelled trypomastigotes were similar and as described previously [34], indicating that CSFE did not interfere with the process of activation or with analyses performed by Xow cytometry (data not shown).…”
Section: Flow Cytometry Analysis Of Leucocytesmentioning
confidence: 59%
“…In a recent work, we also reported that live T. cruzi parasites enhance expression of co-stimulatory surface molecules on cord blood myeloid dendritic cells (mDCs) and that T. cruzi-activated mononuclear cells from cord blood, containing activated mDCs, promote proliferation of CD8 + T cells and type 1-polarized response [34], whereas other studies showed that T. cruzi inhibits the response to lipopolysaccharide (LPS) of monocyte-derived DCs (MoDCs) from adult blood [48,49]. The present work aims to determine the susceptibility of mDCs and other leucocytes to T. cruzi infection and to decipher the role of extracellular versus intracellular, as well as live versus lysed parasites, in activation of cord blood mDCs.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The immunological state of the mother [6,[33][34][35] and fetus [16,[43][44][45][46] may be important for congenital transmission. Hermann et al [33] observed that decreased maternal immune response to parasitic antigens was associated with increased risk of congenital transmission.…”
Section: Epidemiologymentioning
confidence: 99%